Penyuluhan Peningkatan Efisensi Produksi Ternak Ayam Pedaging dan Petelur di Masa Pandemi - Ngitung, Rosdiana; Umar, Muhammad Fitrah Ramadhan; Taiyeb, Mushawwir (Jurnal Abdi Negeriku, 2022)
The problems faced by the family community of broiler and laying hens are as follows: decreasing consumption of broilers and laying hens in the era of the covid 19 pandemic, management of livestock business which is still weak, management and availability of inadequate rations, no effective ration manufacturing technology is carried out, low entrepreneurial knowledge possessed, business financing and production processes are still high, and there is no technology for handling chicken rejects. The results of the data in the field are many broiler and laying hens lower prices. Livestock as a commodity has a high elasticity of demand for income. This problem is also experienced by the people of Pattalassang Village, Tompobulu District, the majority of whom work as farmers and breeders, especially chicken farmers. The methods used are training, mentoring, lectures, practice and demonstrations. The result of this program is increasing public awareness of the importance of skills to increase family income by properly managing existing potential such as raising broilers and laying hens by developing them in the form of entrepreneurship.